MYOFASCIAL RELEASE THERAPY IN ADDITION TO THE POSTERIOR PELVIC TILTING IN HYPERLORDOSIS INDIVIDUALS - Arun B; Suganya M; Adarsh Ashok (Universitas Muhammadiyah Ponorogo, 2019)
Hyperlordosis is excessive curvature of lumbar spine, caused by incorrect posture, muscle weakness, obesity and pregnancy. Management for Hyperlordosis was not shown to be effective. The Aim of the study is to identify the effect of myofascial release therapy, posterior pelvic tilting and abdominal exercises in Hyperlordosis. Single blinded randomized controlled trial involves 69 participants who randomly divided into three groups, MFRG is myofascial release therapy group, PPTG is posterior pelvic tilting group ABEG is abdominal exercise group. Outcomes measured are lordotic angle by Flexible ruler (FR) and Range of motion by Modified Schobers test (MST). Result shows that there was significant difference between the groups. Tukey HSD analysis showed that Q statistics for the FR between MFRG vs PPTG is 13,71 (p0,01%) and MST is 20,34 (p0,01%), FR between PPTG vs ABEG is 5,16 (p0,01%) and MST is 15,35 (p0,01%), FR between MFRG vs ABEG is 8,55 (p0,01%) and MST is 4,99 (p0,01%).PPTG group has showed marked differences when compared with the other two groups (MFRG and ABEG). ABEG also showed significant differences when compared with MFRG. Conclusion of this study was there is a significant difference obtains in the lordotic angle and range of motion in PPTG).